Pengaruh Rasio Likuiditas, Aktivitas, Profitabilitas dan Leverage Terhadap Return Saham Pada Perusahaan Manufaktur Yang Terdapat Di Bursa Efek Indonesia (Studi Kasus pada Perusahaan Tekstil dan Garment Tahun 2011-2014) - Yulitiawati Yulitiawati; Desy Mandela; Hasiatul Aini (STIE DWI SAKTI BATURAJA, 2020)
This study was conducted to determine the effect of liquidity ratios, activity, profitability and leverage on stock return on manufacturing companies listed in Indonesia Stock Exchange (the case study on the textile and garment 2011-2014).The study population were 17 companies with the sampling technique used was purposive sampling method and of 17 companies obtained a sample of 10 companies that meet the criteria. The analytical tool used in this research is multiple linear regression. Based on the analysis and discussion, it can be concluded that only partially profitability ratios significantly influence stock return, while the liquidity ratio, activity ratio and leverage ratio have no significant effect on stock return. The coefficient of determination is equal to 0,135 or 13,5% while the remaining 86,5% influenced or explained by other variables not included in this research model for example, the ratio of market valuation, company size and content of cash flow information. Keywords: Liquidity Ratios, Activity, Profitability, Leverage, and Stock Return